TAMBANG RAKYAT, BERKAH ATAU MUSIBAH? (STUDI TENTANG TAMBANG EMAS RAKYAT DI GUNONG UJEUN KABUPATEN ACEH JAYA) - Aminah Aminah (Universitas Teuku Umar, 2017)
This study aims to explain the gold mining in Gunong Ujeun, Aceh jaya by using the theories of Thomas Homer-Dixon of the environmental scarcity, whether in Gunong Ujeun mining can be categorized as a blessing or a disaster with a view of reality and phenomena that exist in the field. The data in this research was obtained through literature (library research) and field research. The results showed that small-scale gold mining in the region Gunong Ujeun has many benefits, it is a blessing bestowed by the Almighty to the people, especially for people who do the mining. Since 2008 has been a lot of things are changing in the region District of Krueng Sabee, ranging from forests to watersheds in the river. The destruction of the forest will be an impact on other natural resources such as soil cycles are no longer fertile, discoloration and quality of water, as well as damage to the fish that were in the river will die, and as a result of toxic mercury wastes are poured into the river. This caused conflict among the community. It is is a horizontal conflict between migrant and local communities. The cause of it, namely (1) frequent flooding aftermath of the mining (2) more difficult to get fresh fish and the water has been contaminated with mercury and cyanide. (3) government agency that is less concerned with the environment (4) Control of natural resources by immigrant communities. Keywords: Peoples Mining, conflict, environmental degradation.